The Effect of Fast and Slow Rhythm Double Leg Hop Progression Training on Leg Muscle Explosive Power in Volleyball Athletes of the Impeesa Club, North Morowali - Charin Thathyatna Sudamara; Humaedi; Andi Saparia; Andi Sultan Brilin Susandi Eka Wahyudhi (Universitas Tadulako, 2026)
The purpose of this study was to determine whether there is an effect of fast and slow rhythm double leg hop progression training on increasing explosive power of leg muscles. The method used in this study is an experimental method. The population in this study were all volleyball athletes of the North Morowali Impeesa club, totaling 30 people, namely the fast rhythm double leg hop progression group of 15 people, and the slow rhythm double leg hop progression group of 15 people. The results of the study showed an increase in explosive power of leg muscles with the fast rhythm double leg hop progression training method, evidenced by the average difference value of 43.7 - 30.4 with these results showing an increase in the average value of 13.3. While the slow rhythm double leg hop progression training with an average difference of 42.2 - 29.4 with these results showing an increase in the average value of 12.8. From the results of this study, it is proven that the provision of the fast rhythm double leg hop progression training method has a better effect compared to the slow rhythm double leg hop progression training on increasing explosive power of leg muscles in volleyball athletes of the North Morowali Impeesa club.